Graphene-containing composite structure and method for producing the same
Patent Information
- Application Number
- JP2022206531
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2042-12-23
AI Technical Summary
Existing graphene-based catalysts for electrochemical cells, such as water electrolysis devices and fuel cells, exhibit unstable and insufficient catalytic activity due to the inherent instability of defects in the graphene structure.
A composite structure is developed with a graphene multilayer film doped with impurities, such as silicon or boron, on the surface of Ni nanoparticles, where the impurity concentration gradient decreases from the inside toward the surface, and the graphene film is etched to enhance catalytic activity.
The composite structure achieves stable and high catalytic activity by increasing the number of defects and modifying the graphene surface, resulting in improved performance in electrochemical cells.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite structure containing graphene having high catalytic activity, and a method for producing the same. [Background technology]
[0002] In electrochemical cells such as water electrolysis devices, fuel cells, and air secondary batteries, catalysts are used in the electrodes, and platinum is generally used. However, in view of the depletion of metal resources, alternative catalysts are desired, and graphene-based catalysts have been proposed.
[0003] For example, Patent Document 1 discloses a catalyst for a water electrolysis electrode that uses nickel-carbon nano-onion (Ni-CNO), which is made by providing a multilayered film of graphene on the surface of particulate nickel. By applying such a catalyst as a mixed liquid with an ionomer to one side of a carbon cloth that constitutes a gas diffusion layer to form a water electrolysis electrode, it is said that high energy conversion efficiency can be obtained and the electrode can be manufactured inexpensively.
[0004] Patent Document 2 also discloses a method for manufacturing a composite structure made of Ni-CNO as described above by irradiating microwaves. A composition containing silicon carbide, nickel, and zeolite, each of which is a particle, and acting as a catalyst is irradiated with microwaves in a multimode to activate it, and then a hydrocarbon gas such as methane is contacted with the composition to cause a reaction using the carbon compound contained in the hydrocarbon gas as a substrate, thereby supporting graphene on the nickel surface in the composition. Here, one mechanism of the graphene production process is that silicon carbide absorbs microwaves, generates heat by itself, thermally activates nickel, and promotes the thermal decomposition of the carbon compound, while the template structure of zeolite, which has a pore size of the order of an aromatic ring, induces the synthesis of a carbon structure that forms a graphene skeleton, and the carbon growth action of nickel promotes the growth of the 6-membered ring carbon structure of graphene.
[0005] Here, Non-Patent Document 1 describes that defects widely present in nanomaterials become local regions that give catalytic activity, and that the addition (doping) of heteroatoms (impurities) as zero-dimensional point defects becomes defects that give such catalytic activity, and then discusses the experimental results of the catalytic activity of boron-doped carbon nano-onions (CNO). It is said that such CNO is obtained by heat treatment of ultra-dispersed nanodiamond particles and amorphous boron. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2021-46585 [Patent Document 2] JP 2016-64369 A [Non-patent literature]
[0007] [Non-Patent Document 1] ACS Appl. Mater. Interfaces 2021, 13, 51628-51642 Summary of the Invention [Problem to be solved by the invention]
[0008] Introducing defects into graphene can give it catalytic activity. In the Ni-CNO mentioned above, defects are generated by forming a multilayer structure of graphene by applying curvature to the Ni nanoparticles, and catalytic activity can be obtained. However, the catalytic activity is unstable and insufficient. Therefore, it is possible to dope impurities into graphene to further increase its catalytic activity.
[0009] The present invention has been made in consideration of the above-mentioned circumstances, and an object of the present invention is to provide a composite structure including doped graphene having high catalytic activity, and a method for producing the same. [Means for solving the problem]
[0010] The graphene-containing composite structure according to the present invention is characterized in that an impurity-doped graphene multilayer film is provided on the surface of Ni nanoparticles that form a solid solution with carbon.
[0011] This feature allows for high catalytic activity in Ni-CNO.
[0012] In the above-mentioned invention, the impurity may be silicon or boron. The graphene multilayer film may have a gradient in which the concentration of the impurity decreases from the inside to the surface. With this feature, stable and high catalytic activity can be obtained in Ni-CNO.
[0013] The graphene multilayer film may be characterized in that it has an etched surface. The graphene multilayer film may also be characterized in that the G / D ratio of the Raman spectrum of the graphene multilayer film is greater than 1.30. According to this feature, a new surface is provided to the graphene multilayer film of Ni-CNO, and stable high catalytic activity can be obtained.
[0014] In addition, the manufacturing method according to the present invention is a method for manufacturing a composite structure in which an impurity-doped graphene multilayer film is applied to the surface of Ni nanoparticles that have carbon as a solid solution, and is characterized in that a mixture of a nanometal powder made of Ni, a metal carbide heated by microwaves, and a zeolite-based catalyst is adjacent to a susceptor that contains an impurity source that provides the impurities and is heated by microwaves, and a reaction gas containing hydrocarbons and carbon dioxide is circulated while irradiating microwaves.
[0015] According to this feature, a catalyst made of Ni-CNO having high catalytic activity can be obtained stably.
[0016] In the above-mentioned invention, the susceptor may be made of silicon carbide. The reactive gas may further contain hydrogen sulfide. Or, the susceptor may be made of boron oxide. According to such a feature, a catalyst made of Ni-CNO having high catalytic activity can be obtained more stably.
[0017] In the above-mentioned invention, the method may further include an etching step of etching the surface of the graphene multilayer film on the surface of the Ni nanoparticles after stopping the flow of the reaction gas. The etching step may be performed by gas-phase chemical etching using carbon dioxide. According to this feature, a catalyst made of Ni-CNO having higher catalytic activity can be stably obtained.
[0018] In the above-mentioned invention, the hydrocarbon may be methane. According to this feature, a catalyst made of Ni-CNO having high catalytic activity can be obtained more stably.
[0019] In the above-mentioned invention, the metal carbide and the zeolite catalyst may be a molybdenum carbide and NZSM-5, respectively. According to this feature, a catalyst made of Ni-CNO having high catalytic activity can be obtained more stably. [Brief description of the drawings]
[0020] [Figure 1] This is a TEM image of Ni-CNO. [Diagram 2] FIG. 2 is a cross-sectional view showing the internal configuration of a reaction tube. [Diagram 3] 1 is a graph showing the relationship between the distance from a Ni nanoparticle surface of a graphene multilayer film and the Si concentration, as measured by a STEM-EDX method. [Figure 4] This is a photoelectron spectrum obtained by X-ray photoelectron spectroscopy. [Diagram 5] TEM image of a graphene multilayer film after CO2 etching. [Figure 6] Raman spectra of graphene multilayers after CO2 etching. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] A composite structure as one embodiment of the present invention will be described with reference to FIGS. 1 to 6. FIG.
[0022] As shown in Fig. 1, the composite structure 1 according to this embodiment includes a graphene multilayer film 3 doped with impurities on the surface of a Ni nanoparticle 2 in which carbon is dissolved. In other words, it has a nickel carbon nano-onion (Ni-CNO) structure in which the Ni nanoparticle 2 is a central core and the graphene multilayer film 3 doped with impurities is provided around the central core in the shape of a shell. As the impurity, for example, silicon or boron can be suitably used.
[0023] The composite structure 1 is obtained by generating defects in the graphene structure by imparting curvature to the graphene multilayer film 3 and further increasing or generating defects in the graphene structure by doping with impurities. The composite structure 1 can obtain a stable high catalytic activity due to its structure having a stable number of defects.
[0024] As shown in Fig. 2, a reaction tube 10 can be used as a method for producing such a composite structure 1. Inside the reaction tube 10, catalyst layers 11 and susceptor layers 12 are alternately stacked so as to be adjacent to each other. The catalyst layer 11 contains a mixture of nanometal powder made of Ni, metal carbide heated by microwaves, and a zeolite catalyst. The susceptor layer 12 contains an impurity source that provides impurities and a susceptor that is heated by microwaves.
[0025] The reaction tube 10 is installed in a microwave reactor having a frequency of 0.3 to 3.0 GHz, typically 2.45 GHz, of a single mode or multimode type, so that the susceptor layer 12 and the like inside can be heated by microwaves. In addition, the reaction gas can be introduced from the top of the reaction tube 10, circulated inside, and discharged from the bottom. The reaction gas contains a hydrocarbon. As the hydrocarbon, methane can be preferably used. In order to circulate the reaction gas, the catalyst layer 11 and the susceptor layer 12 are each formed in a shape that allows the reaction gas to flow. For example, by laying each material in a gravel shape, a layer that allows the reaction gas to flow can be obtained relatively easily. Note that the reaction gas is not necessarily required to flow from the top to the bottom, since it is partially convected and diffused inside the reaction tube 10, and other flow directions, such as introduction from the side, may be used.
[0026] When the reaction gas is introduced while irradiating the reaction tube 10 with microwaves to heat the susceptor layer 12, the impurity source is heated and decomposed to liberate the impurity atoms, and the hydrocarbons in the reaction gas are decomposed by the catalyst layer 11. Then, the decomposed C takes in the impurity atoms and forms a multilayered film of graphene on the surface of the nanometal powder. That is, the carbon derived from the hydrocarbons that could not be dissolved in the Ni nanoparticles 2 as nuclei under the thermal environment is formed in layers together with the impurities as dopants. In this way, a composite structure 1 in which the graphene multilayered film 3 is doped with impurities can be obtained.
[0027] The susceptor layer 12, which serves as a heating source by microwave irradiation, may be disposed inside the catalyst layer 11, or may be mixed therewith, so as to be adjacent to each other as appropriate.
[0028] For example, a detailed description will be given of an example in which the composite structure 1 is obtained by doping with silicon (Si) as an impurity.
[0029] In the catalyst layer 11, Ni powder having a particle size of 150 nm or less (for example, 20 to 150 nm) was used as the nanometal powder, and molybdenum carbide, which is a carbide of molybdenum, was used as the metal carbide. Here, the particle size of the nanometal powder can be determined by the following method. That is, the particles of the nanometal powder to be measured were observed with a scanning transmission electron microscope, and the short diameter and long diameter of each particle were measured, and the average value was taken as the particle size of the particle. In the same manner, the particle sizes of 100 particles were determined, and the average value was taken as the particle size of the nanometal powder.
[0030] In addition, H-type ZSM-5 (weight ratio of silicon dioxide / alumina is 23) was used as the zeolite catalyst. In the susceptor layer 12, silicon carbide (β-SiC) was used as the susceptor. Silicon carbide contains silicon, which is an impurity element that serves as a dopant, and silicon carbide also serves as an impurity source that supplies silicon. A quartz tube was used as the reaction tube 10. The reaction tube 10, in which the catalyst layer 11 and the susceptor layer 12 were stacked adjacent to each other inside, was installed in a microwave reactor. A multi-mode microwave generator (μ-Reactor-Ex, manufactured by Shikoku Keisoku Kogyo Co., Ltd., magnetron transmission frequency: 2.45 GHz, maximum transmission power: 1 kW) was used as the microwave reactor.
[0031] While introducing methane as a reactive gas from the top of the reaction tube 10, the reaction tube 10 was irradiated with microwaves from a microwave reactor. This resulted in the production of a composite structure 1 (hereinafter, Ni-CNO) having a silicon-doped graphene multilayer film.
[0032] The obtained Ni-CNO is mixed with the catalyst components consisting of the metal carbide and zeolite catalyst used in the catalyst layer 11, and can be separated from them. For example, it can be separated by washing using a liquid-liquid interface and pickling. In detail, the process of dispersing Ni-CNO with the catalyst components in a mixture liquid in which a liquid-liquid interface is formed by distilled water and toluene, and removing the distilled water is repeated several times. Then, the Ni-CNO taken into the oil phase by toluene is filtered, washed with distilled water and ethanol, and dried. Furthermore, it is put into 30% hydrogen peroxide water heated in a hot water bath and stirred for 30 minutes. After that, it is filtered and washed with distilled water and ethanol, so that Ni-CNO can be separated from the catalyst components.
[0033] On the other hand, when the composite structure 1 is obtained by doping with boron (B) as an impurity, solid boron oxide (BO) is used for the susceptor layer 12, and boron as an impurity is supplied from this boron oxide. Methane is used as the reaction gas, but it is preferable to mix carbon dioxide. Carbon dioxide etches the boron oxide, thereby promoting the decomposition of the boron oxide and the doping of boron. The composite structure 1 doped with boron can be obtained in the same manner as above. Similarly, boron carbide or boron nitride can also be used as a susceptor for supplying boron as an impurity. When the reaction gas contains both a hydrocarbon (preferably methane) and carbon dioxide, the content of carbon dioxide relative to the total volume of the hydrocarbon and hydrogen sulfide is preferably 20 to 80 volume %, more preferably 40 to 60 volume %.
[0034] Below, we will explain the results of a more detailed investigation of Ni-CNO obtained using silicon as a dopant.
[0035] Here, as shown in FIG. 3, the concentration of impurities was investigated when methane and hydrogen sulfide were mixed at a volume ratio of 50% each as the reaction gas. The amount of silicon in the range from the surface (Ni side) of the Ni nanoparticles 2 to the surface (CNO side) of the graphene multilayer film 3 (CNO) in Ni-CNO was measured by energy dispersive X-ray spectroscopy (STEM-EDX method) in a scanning transmission electron microscope. According to the figure, when hydrogen sulfide was included in the reaction gas (introduced gas), the amount of doped silicon increased by about three times compared to when hydrogen sulfide was not included. This is because the supply amount of silicon, which is a dopant, was increased by etching silicon carbide with hydrogen sulfide. This promotes the doping of silicon into Ni-CNO, and as a result, the doped amount of silicon increases. In other words, it is also preferable that hydrogen sulfide is included as a reaction gas. When the reaction gas contains both a hydrocarbon (preferably methane) and hydrogen sulfide, the content of hydrogen sulfide relative to the total volume of the hydrocarbon and hydrogen sulfide is preferably 20 to 80% by volume, and more preferably 40 to 60% by volume.
[0036] As shown in the figure, the silicon concentration tends to decrease from the surface of the Ni nanoparticles 2 toward the surface of the graphene multilayer film 3. In this way, the graphene multilayer film 3 may have a gradient in which the impurity concentration decreases from the inside toward the surface.
[0037] It is also preferable that the graphene multilayer film 3 has an etched surface. That is, Ni-CNO having an etched surface can be obtained by adding an etching step to the above manufacturing method. Specifically, Ni-CNO doped with silicon is immersed in an aqueous hypochlorous acid solution at room temperature for several tens of hours. The Ni-CNO etched in this way and the Ni-CNO that was not etched were subjected to energy analysis by X-ray photoelectron spectroscopy to obtain photoelectron spectra.
[0038] As shown in Figure 4, the photoelectron spectrum obtained showed that almost no clear peaks were observed without etching, whereas a clear peak corresponding to the impurity Si was observed with etching. It is believed that etching creates a new surface of CNO, causing a change in the properties of the surface. That is, the properties of the surface of CNO formed by regular growth due to carbon deposition and the etched surface formed by erosion from chemically selected sites can be different. As a result, etching can increase the silicon concentration of the surface, resulting in stable and higher catalytic activity. In addition, as mentioned above, the silicon concentration tends to increase toward the inside of CNO, and etching the surface to move it toward the inside of CNO is preferable because it is possible to increase the silicon concentration of the new surface. In addition, the closer to the surface of the Ni nanoparticles, the higher the curvature of graphene becomes, and the number of defects per unit area also increases. It is believed that etching can also increase catalytic activity in this respect.
[0039] The etching process may be a known wet etching process using a hot mixed acid or a dry etching process. For example, it may be a gas-phase chemical etching process using carbon dioxide. In the above-mentioned method for producing Ni-CNO, after the formation of Ni-CNO, the flow of the reaction gas is stopped, and then carbon dioxide is circulated through the reaction tube 10 and microwaves are irradiated. Then, CNO is etched from the surface by the Boudouard reaction.
[0040] As shown in FIG. 5, the etching state according to the flow time of carbon dioxide was compared. Here, the mass of the catalyst layer 11 was about 20 g, and carbon dioxide was flowed at 50 mL / min. As shown in FIG. 5(a), when the flow time was set to 50 minutes, 60 to 80 layers of graphene of CNO remained, resulting in a layer thickness of about 50 to 100 nm, and depending on the particle size of Ni nanoparticles, the particles became spherical with a particle size of about 100 to 200 nm. Also, as shown in FIG. 5(b), when the flow time was set to 150 minutes, 30 to 50 layers of graphene of CNO remained, resulting in a layer thickness of several tens of nm, and a particle size of about 50 to 100 nm. Furthermore, as shown in FIG. 5(c), when the flow time was set to 300 minutes, 10 to 30 layers of graphene of CNO remained, resulting in a layer thickness of about 10 nm, which is thinner than the diameter of Ni nanoparticles, and a particle size of about 20 to 100 nm. This shows that the etching is promoted by heating and circulating carbon dioxide. The particle size of Ni-CNO can be measured in the same way as the particle size of nanometal powder.
[0041] As shown in Figure 6, the Raman spectra of CNO were measured at the three flow times mentioned above, and the peak at 1,350 cm -1 The peak intensity ratio (G / D ratio) of the D-band, which is a nearby vibration mode, and the G-band, which is a vibration mode similar to the Raman active mode of graphite, was calculated to evaluate the amount of defects introduced. The G / D ratio increases as the flow time of carbon dioxide increases. This result shows that the etched surface by dry etching can also change the surface properties of CNO. In order to obtain stable and high catalytic activity, it is desirable to make the G / D ratio in the Raman spectrum of CNO by etching greater than 1.10, preferably greater than 1.30, and more preferably greater than 1.50. The upper limit of the G / D ratio is not particularly limited, but is, for example, 2.50 or less.
[0042] Although the embodiments of the present invention and modifications based thereon have been described above, the present invention is not necessarily limited to these examples. In addition, a person skilled in the art will be able to find various alternative embodiments and modifications without departing from the spirit of the present invention or the scope of the appended claims. [Explanation of symbols]
[0043] 1 Composite structure 2. Ni nanoparticles 3. Graphene multilayer film 10 Reaction tube 11 Catalyst layer 12 Susceptor layer
Claims
1. A composite structure in which a graphene multilayer film doped with impurities is provided on the surface of Ni nanoparticles in which carbon is dissolved, the impurity is silicon or boron; The graphene multilayer film has a gradient in which the concentration of the impurities decreases from the inside toward the surface.
2. The graphene-containing composite structure according to claim 1 , wherein the graphene multilayer film has an etched surface.
3. 3. The graphene-containing composite structure according to claim 2, wherein the graphene multilayer film has a G / D ratio in a Raman spectrum of more than 1.
30.
4. A method for producing a composite structure in which a graphene multilayer film doped with impurities is provided on a surface of Ni nanoparticles having carbon dissolved therein, the method comprising the steps of: A method for producing a composite structure containing graphene, comprising: placing a mixture of a nanometal powder made of Ni, a metal carbide heated by microwaves, and a zeolite-based catalyst adjacent to a susceptor made of silicon carbide and containing an impurity source that provides the impurities and is heated by microwaves; and irradiating microwaves while passing a reaction gas containing hydrocarbons and hydrogen sulfide through the mixture.
5. A method for producing a composite structure comprising providing a graphene multilayer film doped with impurities on a surface of Ni nanoparticles having carbon as a solid solution, the method comprising the steps of: A method for producing a composite structure containing graphene, comprising: placing a mixture of a nanometal powder made of Ni, a metal carbide heated by microwaves, and a zeolite-based catalyst adjacent to a susceptor made of boron oxide and containing an impurity source that provides the impurities, and heated by microwaves; and flowing a reaction gas containing a hydrocarbon while irradiating microwaves.
6. 6. The method for producing a graphene-containing composite structure according to claim 4, further comprising an etching step of etching a surface of the graphene multilayer film on a surface of the Ni nanoparticles after the flow of the reaction gas is stopped.
7. The method for producing a graphene-containing composite structure according to claim 6, wherein the etching step is performed by gas phase chemical etching using carbon dioxide.
8. The method for producing a composite structure including graphene according to claim 4 or 5, characterized in that the hydrocarbon is methane.
9. The method for producing a graphene-containing composite structure according to claim 4 or 5, wherein the metal carbide and the zeolite-based catalyst are molybdenum carbide and H-type ZSM-5, respectively.